Identification of Acanthamoeba spp. from water and soil of public parks in the north of Iran. (21st September 2022) - Mahmoudi, M. R.; Maleki, M.; Zebardast, N.; Rahmati, B.; Ashrafi, K.; Sharifdini, M.; Karanis, Panagiotis
Abstract: Acanthamoeba, a free-living and opportunistic protozoan parasite, is a causative agent of severe human infections of the cornea and brain. The present study evaluated the distribution and genotyping of Acanthamoeba spp. in water and soil of recreational places in various areas in Guilan province in northern Iran. Eighty water and 20 soil samples were collected from the study area. Water samples were vacuum filtered through a 0.45 μm pore-size membrane filter. Soil samples were washed with sterile distilled water, and washings were similarly filtered, as mentioned for water samples. The filtered material was cultured on non-nutrient agar plates seeded with heat-killed Escherichia coli . Molecular analysis was performed by PCR and sequencing using specific primers for Acanthamoeba . Finally, 26 isolates were successfully sequenced. According to culture and PCR methods, 54% of water and 100% of soil samples were contaminated with Acanthamoeba . Based on the sequencing data, genotypes T4 (47%), T5 (35.29%), T3 (11.76%), and T11 (5.88%) were identified in water samples. Genotypes T4 (66.6%), T5 (22.2%) and T15 (11.1%) were identified in water samples. Most isolates might present a potential health hazard for humans in this region. To the best of our knowledge, this is the first comprehensive survey of water and soil of recreational areas in northern Iran and the first report on identifying genotype T15 from soil sources. HIGHLIGHTS: Acanthamoeba detected in entertainments environmental samples. Pathogenic genotypes of Acanthamoeba detected in the soil of public entertainment parks. Hygiene and policies are necessary to protect humans against Acanthamoeba infections.